Pokdarwis Assistance in Establishing Educational Tourism Through The Grafting and Planting Pine Tree Program at Wonderfull Bimorejo Beach - Nawal Ika Susanti; Anyes Lathifatul Insaniyah (CENDEKIA: Jurnal Pengabdian Masyarakat, 2024)
The aim of this service program is to create an educational tourist attraction at Bimo Beach together with the Wongsorejo District Pokdarwis by planting and transplanting 1000 pine trees targeting schools around the Wonderful Bimorejo beach. This service uses an Asset Based Community Development (ABCD) approach. As a result of this dedication, Bimo Beach has successfully planted 522 pine trees. The success of this program can be seen from the formation of an MOU between Pokdarwis and Educational Institutions, the ongoing program of grafting and planting a thousand pine trees as one of the educational tourism attractions, as well as the existence of a tour guide who can explain the process of grafting and planting pine trees to tourists visiting Bimo Beach. to enjoy educational tourism.